Beam-column modeling and seismic fragility analysis of a prestressed segmental concrete tower for wind turbines. Issue 8 (June 2020) - Cao, Yuqi; He, Minjuan; Ma, Renle; Yang, Rongchang; Liang, Feng
As the development of wind energy in earthquake areas advances, the seismic performance of concrete supporting towers has become an important subject. A beam-column model is developed for a prestressed segmental concrete tower supporting a wind turbine considering the properties of dry joints. The proposed model is in good agreement with the solid element model deformation results and the field test modal results. Based on the beam-column model, nonlinear time history analyses considering uncertainties are conducted to evaluate the behavior of the prototype tower under earthquake action. In the process, a new engineering demand parameter, called the average curvature, is defined. The results are compared with those based on a conventional engineering demand parameter. The availability of the prototype tower under earthquake action and the effectiveness of the newly defined engineering demand parameter are validated.